Dual Roles for NFAT Transcription Factor Genes as Oncogenes and Tumor Suppressors - Robbs, Bruno K. (American Society for Microbiology (ASM), 2008)
Nuclear factor of activated T cells (NFAT) was first described as an activation and differentiation transcription factor in lymphocytes. Several in vitro studies suggest that NFAT family members are redundant proteins. However, analysis of mice deficient for NFAT proteins suggested different roles for the NFAT family of transcription factors in the regulation of cell proliferation and apoptosis. NFAT may also regulate several cell cycle and survival factors influencing tumor growth and survival. Here, we demonstrate that two constitutively active forms of NFAT proteins (CA-NFAT1 and CA-NFAT2 short isoform) induce distinct phenotypes in NIH 3T3 cells. Whereas CA-NFAT1 expression induces cell cycle arrest and apoptosis in NIH 3T3 fibroblasts, CA-NFAT2 short isoform leads to increased proliferation capacity and induction of cell transformation. Furthermore, NFAT1-deficient mice showed an increased propensity for chemical carcinogen-induced tumor formation, and CA-NFAT1 expression subverted the transformation of NIH 3T3 cells induced by the H-rasV12 oncogene. The differential roles for NFAT1 are at least partially due to the protein C-terminal domain. These results suggest that the NFAT1 gene acts as a tumor suppressor gene and the NFAT2 short isoform acts gene as an oncogene, supporting different roles for the two transcription factors in tumor development.